Change of body weight and macrophage inhibitory cytokine-1 during chemotherapy in advanced gastric cancer: what is their clinical significance? - Zhihao Lu; Li Yang; Jingwei Yu; Ming Lu; Xiaotian Zhang; Jian Li; Jun Zhou; Xicheng Wang; Jifang Gong; Jing Gao; Jie Li; Yan Li; et al. (PLoS ONE)
Background Weight loss in advanced gastric cancer (GC) has been widely acknowledged to be a predictor for poor survival. However, very few studies have investigated the weight loss that occurs during chemotherapy. Therefore, we focused on weight loss during chemotherapy in patients with advanced GC and investigated the concentrations of macrophage inhibitory cytokine-1 (MIC-1), which has been recognized as a probable etiological factor in anorexia and weight loss. Methods We analyzed 384 patients with inoperable locally advanced or metastatic GC receiving first-line chemotherapy. Patients were assigned to one of two groups on the basis of their weight change during chemotherapy: >3% weight loss and ≤ 3% weight loss. Serum MIC-1 and C-reactive protein (CRP) concentrations were also assessed in these patients. Results The >3% weight loss group had shorter overall survival (OS; 12.0 months vs. 17.5 months, P = 0.000) than the ≤ 3% weight loss group, and the survival rates improved if the weight loss was reversed during chemotherapy. Although the MIC-1 concentrations were not correlated with weight loss before (P = 0.156) or during chemotherapy (P = 0.164), it correlated significantly with the CRP concentration (P = 0.001). Furthermore, elevated MIC-1 concentrations before chemotherapy (P = 0.017) and increased MIC-1 concentrations during chemotherapy (P = 0.001) were both found to be predictors of poor OS. Conclusions Changes in the body weight during chemotherapy could influence the prognosis in patients with advanced GC, and the MIC-1 might be a potential predictive and prognostic biomarker in those patients.